Metabolic Changes Preceding Exercise-induced Bronchoconstriction. Issue 5794 (22nd January 1972) - Silverman, M.; Anderson, Sandra D.; Walker, S. R.
Abstract : Five asthmatics aged 25-30 were studied during bicycle ergometer and treadmill exercise. Metabolic and ventilatory changes during exercise were compared with the degree of bronchoconstriction which followed exercise. In all patients bronchoconstriction was greater after treadmill exercise. Contrary to previous suggestions, exercise-induced bronchoconstriction did not seem to be caused by lactic acidosis, increase in minute ventilation, acidaemia, hypocapnia, or change in arterial Po2